2020
DOI: 10.3390/biom10030441
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Dysregulates Skeletal Muscle Myogenic Gene Expression after Hind Limb Immobilization in Female Rats

Abstract: Alcohol use and aging are risk factors for falls requiring immobilization and leading to skeletal muscle atrophy. Skeletal muscle regeneration is integral to post-immobilization recovery. This study aimed to elucidate the effects of alcohol and ovarian hormone loss on the expression of genes implicated in muscle regeneration. Three-month-old female rats received an ovariectomy or a sham surgery, consumed an alcohol-containing or control diet for 10 weeks, were subjected to unilateral hind limb immobilization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…TNF-α levels in injured muscle have been shown to rise dramatically due to a strong increase in its synthesis by injured myofibrils and its release by infiltrating inflammatory cells [ 12 , 13 , 14 , 15 ]. While a transient increase in intramuscular TNF-α levels after injury is required for muscle regeneration and repair, a persistent high concentration of this mediator inhibits myogenesis and limits recovery, leading to muscle wasting [ 8 , 16 , 17 ]. Increased synthesis of TNF-α, observed in the early phase of differentiation of C2C12 myoblasts in culture, is positively associated with regeneration, since its inhibition prevents the process of muscle repair [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α levels in injured muscle have been shown to rise dramatically due to a strong increase in its synthesis by injured myofibrils and its release by infiltrating inflammatory cells [ 12 , 13 , 14 , 15 ]. While a transient increase in intramuscular TNF-α levels after injury is required for muscle regeneration and repair, a persistent high concentration of this mediator inhibits myogenesis and limits recovery, leading to muscle wasting [ 8 , 16 , 17 ]. Increased synthesis of TNF-α, observed in the early phase of differentiation of C2C12 myoblasts in culture, is positively associated with regeneration, since its inhibition prevents the process of muscle repair [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a transient increase in intramuscular TNF-α levels after injury is required for muscle regeneration and repair, a persistent high concentration of this mediator inhibits myogenesis and limits recovery, leading to muscle wasting [ 8 , 16 , 17 ]. Increased synthesis of TNF-α, observed in the early phase of differentiation of C2C12 myoblasts in culture, is positively associated with regeneration, since its inhibition prevents the process of muscle repair [ 16 , 18 ]. In parallel to TNF-α release, an increased expression of TNF-α receptors is found in injured muscle fibres [ 13 , 14 ], which has been shown to regulate the exiting of the cell cycle and the initiation of myogenic differentiation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle recovery may be complicated by alcohol use and altered hormonal status among older individuals (Lukaszyk et al, 2016). To examine this question, we utilized Lieber-DeCarli feeding in rats for 10 weeks culminating in 1 week of unilateral hind limb immobilization followed by 3 or 14 days of remobilization (Levitt et al, 2020c). Our data indicated that alcohol dysregulates the expression of markers of muscle regeneration following unilateral hind limb immobilization.…”
Section: Muscle Stem Cell Regenerative Capacitymentioning
confidence: 94%
“…The most common diet used is the Lieber-DeCarli diet (Lieber and DeCarli,1989) and the control diet is isocalorically matched to the alcohol calories. This strategy is widely used to study end-organ injury, including chronic alcohol-induced skeletal muscle pathology (Levitt et al, 2020c;Crowel et al, 2016;Lang, 2018).…”
Section: Alcohol Administration In Rodentsmentioning
confidence: 99%
“…We previously observed that in vivo chronic binge alcohol administration decreases the in vitro differentiation potential of myoblasts isolated from simian immunodeficiency virus (SIV)‐infected (Simon et al, 2017) or SIV‐naïve male rhesus macaques (Simon et al, 2014) and that in vitro ethanol (EtOH) treatment (50mM) decreases the differentiation potential of myoblasts from male macaques assessed at 5 days of differentiation (Adler et al, 2019). Furthermore, our studies in a rodent model of hindlimb immobilization demonstrated that chronic alcohol feeding suppressed SKM expression of myogenic genes at 3 days after remobilization following 1 week of immobilization (Levitt et al, 2020). However, whether alcohol similarly impairs in vitro myoblast differentiation potential in females is unknown.…”
mentioning
confidence: 91%